UPAYA MENINGKATAN HASIL BELAJAR PKN MELALUI METODE DISKUSI UNTUK MATERI SISTEM PEMERINTAHAN DESA DAN KECAMATAN PADA SISWA KELAS IV SD NEGERI SOTOI TAHUN PELAJARAN 2021/2022 - Mikhael Kolo (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
The problem in this research is: How do you apply the discussion method in Civics learning to the material on village and sub-district government systems? and how does the application of the discussion method influence the material on village and sub-district government systems in an effort to improve student learning outcomes? Based on the formulation of the problem above, the goal to be achieved is to apply the discussion method in Civics learning, especially the Village and Sub-District Government System material, to determine the effect of applying the discussion method to the Village and District Government System material in an effort to improve student learning outcomes. Before the improvement of learning from 31 students who had completed learning, only 6 students or 19% and 25 students or 81% had not completed it. This shows a failure in learning. In improving learning cycle I using the discussion method in which each group consists of 6-7 students. Evaluation results obtained from 31 students, there were 15 students who scored 75 and above or 48% of students had completed their studies, while 16 students or 52% of students had not yet completed their studies. The average score obtained in the learning improvement cycle I compared to before the learning improvement was increased, from 55.5 to 67.9 or there was an increase in value of 12.4. In cycle II the researcher used the discussion method with the number of each discussion group being 5 students. In addition, researchers also use media such as fast food, soft drinks, etc. This is in accordance with the opinion of experts about the use of learning media or teaching aids to help students in the learning process.Researchers obtained results on improving learning cycle II. Of the 31 students, all students have completed their studies, with a score of 75 and above, and the average score is 81.8. Seeing the results that have been obtained, the researchers did not make improvements to the third cycle of learning in Civics class IV subjects with village and sub-district governance systems at SDN Sontoi. Key words: Discussion, Learning Outcomes